Transgenerational Holocaust Memory In Slovakia: From Forgetting to Ambivalence About the Roots of Hatred - Juraj Buzalka; Katarína Očková (Studia Humanistyczne AGH)
This article explores Holocaust memory in Slovakia, shedding light on how Slovak citizens perceive this past and its transgenerational transmission. The data presented were gathered in 2023 through ethnographic fieldwork and focus group interviews with informants belonging to three generations (between ages of 18 and 95), in three different locations across the country: Krupina, Prešov, and Bratislava. The initial findings show that Slovakia has been moving from indifference towards the Holocaust to the limited capability of realizing the actual causes and effects of atrocities, while at the same time officially accepting the commemorative centrality of the Holocaust.